(untitled) (Forum Penelitian Agro Ekonomi, 2016)
The fast growing trend of world coffee production in the world creates an excess of its supply, encouraging a more intense of competition among the exporting countries. This situation leads to a decreasing trend of fluctuate price of world coffee. The objective of this paper is to assess the world coffee market behavior in order to make an appropriate strategy and direction of coffee industry policies. Indonesia’s market share in traditional market tends to decrease, and therefore, it is necessary to diversify market destination and commodity composition, in addition to efforts to increase the export of processed coffee.